ЯНГИ ЎЗБЕКИСТОН: ЯНГИ ТАРБИЯНИНГ КОНЦЕПТУАЛ АСОСЛАРИ - Қадиров, Қ. (SCIENCE and SOCIETY, 2019)
This article focuses on the essence of the recently adopted concept of Continuing Spiritual Education in Uzbekistan and its role in the development of our society and the education of youth.
Keywords: new Uzbekistan; national idea; continuous spiritual education; concept; patriotism; loyalty to motherland; higher education; student youth; five important initiatives; bases of spirituality